PERLINDUNGAN HUKUM TERHADAP RELAWAN KEMANUSIAN BERDASARKAN HUKUM HUMANITER INTERNASIONAL - Lona Puspita (Fakultas Hukum Universitas Tamansiswa Padang, 2017)
In humanitarian law there are two forms of war or armed conflict, namely armed conflicts that are international and non-international. In its development, the notion of international armed conflict was expanded in Protocol I of 1977 which also included resistance to colonial domination, the struggle against foreign occupation and resistance to the racialist regime as other forms of international armed conflict. In the midst of the international news about the armed conflict between the two countries is an interesting that is about humanitarian volunteers. Although to help civilians who are in the middle of the conflict based on humanity, a volunteer not infrequently has to bet on his body spirit. This is often experienced by a person or group of humanitarian volunteers who work in the middle of the armed conflict area for the realization of a sense of humanity and caring for others. Not a few armed conflicts that cause humanitarian volunteers either independently or are under a humanitarian organization that is killed, wounded, disappeared and captured or taken hostage.